Predictors of vocational activity over the first year in inner‐city early intervention in psychosis services. Issue 6 (20th February 2014) - Tapfumaneyi, Andrew; Johnson, Sonia; Joyce, John; Major, Barnaby; Lawrence, Jo; Mann, Farhana; Chisholm, Brock; Rahaman, Nikola; Wooley, James; Fisher, Helen L.; MiData Consortium
Abstract Aim Work and educational activities are an important part of recovery for young people with psychosis, and improving vocational outcomes is a key target for early intervention services (EIS). This study evaluated predictors of vocational activity for first‐episode psychosis (FEP) patients during the first year of EIS care. It was hypothesized that longer duration of untreated psychosis (DUP) and minority ethnic status would predict poorer vocational outcomes, whereas a history of good vocational functioning would predict better vocational functioning during follow up. Methods FEP patients aged 14–35 years, who presented to seven EIS in London, UK, between 2003 and 2010, were followed for 1 year. Sociodemographic, clinical and vocational information (qualifications obtained and paid employment) were collected using the MiData audit tool at entry to EIS and 1 year later. Results Approximately one‐third of patients (n = 345/1013) were studying or employed at some point during the first year of EIS care. Baseline vocational activity was the strongest predictor of vocational functioning during 1 year of follow up. Moreover, employment prior to entry into EIS strongly predicted change in vocational activity during 1 year of follow up. Individuals with DUP <6 months or of Asian or black African origin were more likely to be studying than their white British counterparts. Conclusion This study confirms that a significant proportion of FEP patients are able to engage in meaningful vocational activities even within the first year of EIS care. However, services need to focus more resources on getting patients with poor educational or employment histories into training programmes to improve their vocational outcomes.